2016
DOI: 10.1021/acs.cgd.5b01235
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Crystal Formation in the Presence of Polysaccharide

Abstract: Natural polysaccharides play an important role in the formation of nanohydroxyapatite (nHA) crystals in biological systems. In this study, we synthesized nHA crystals in the presence of four polysaccharides, i.e., pectin, carrageenan, chitosan, and amylose, referred as PeHA, CaHA, CsHA, and AmHA, respectively. X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscopy, scanning electron microscope, and thermogravimetric analysis were used to investigate the formation of nHA cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 46 publications
8
64
0
1
Order By: Relevance
“…On the other hand, the non-stoichiometric HAp structures were analysed in both films prepared with lower content of CNF (0.5CNF): A phosphorus-rich (calcium-deficient) HAp with Ca/P ration of 1.56 on the CNF prepared with 100HAp was in agreement with reported literature (Fang et al 2016), and a calcium-rich (phosphorus-deficient) with Ca/P of 1.77 on the film prepared with 25HAp.…”
Section: Films' Characterizationsupporting
confidence: 85%
“…On the other hand, the non-stoichiometric HAp structures were analysed in both films prepared with lower content of CNF (0.5CNF): A phosphorus-rich (calcium-deficient) HAp with Ca/P ration of 1.56 on the CNF prepared with 100HAp was in agreement with reported literature (Fang et al 2016), and a calcium-rich (phosphorus-deficient) with Ca/P of 1.77 on the film prepared with 25HAp.…”
Section: Films' Characterizationsupporting
confidence: 85%
“…However, carrageenan offers advantages over cellulose: unlike cellulose, the former biopolymer is highly soluble in water and dismisses the need for chemical and/or physical modification to its structure to obtain homogeneous hydrogels. Furthermore, the presence of sulfate groups in carrageenan provides it with the potential to mimic the negatively charged macromolecules, like glycosaminoglycans (GAGs), present in the bone extracellular matrix . In addition, regarding hybrid material formation, Zhu et al .…”
Section: Introductionmentioning
confidence: 99%
“…We seek to evaluate how the organic matrix influences mineral phase formation by changing the HC and ι‐Carr ratio used to prepare the membrane. The negatively charged −OSO 3 − groups in the ι‐Carr structure serve as binding sites for Ca 2+ ions and engage in hydrogen bonding with PO 4 3− and H 2 O on the mineral surface, which is suitable for in situ biomineral heterogeneous nucleation. Indeed, the literature highlights that the presence of many nucleation sites, including −OSO 3 Ca + and (−OSO 3 ) 2 Ca, in the matrix consisting of ι‐Carr favors crystal growth .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the band at 1598 cm -1 in CS was related to N-H amide I [21] and this band in CS was shifted to lower wave number in all nanocomposites as shown in Fig.1 (B, C, D and E) due to the interaction of CS with HA [22]. This shift was previously attributed to the binding of chemical function groups of CS (−NH 2 and −NHCO−) and PO 4 3− via electrostatic interaction or Ca 2+ via coordination bond [23]. Finally in the case of acrylic acid, the band at 1598 cm -1 suffered smaller shift which indicated that the in situ formed HA did not have strong interaction with CS's amino groups.…”
Section: Resultsmentioning
confidence: 56%